Two-dimensional model of flow and transport in porous media: Linking heterogeneous anisotropy with stratal patterns in meandering tidal channel deposits of the Venice Lagoon (Italy). (November 2022) - Bachini, Elena; Bellizia, Elena; Putti, Mario; D'Alpaos, Andrea; Ghinassi, Massimiliano
Abstract: Understanding the internal structure of permeable and impermeable sediments (e.g. point-bars and tidal-flat deposits) generated by the evolution of meandering tidal channels is essential for accurate modeling of groundwater flow and contaminant transport in coastal areas. The detailed reconstruction of stratal geometry and hydraulic properties from measurements must be accompanied by depositional history information. In this work, we use high resolution reconstructions of ancient tidal channels of the Venice Lagoon (Italy) to drive 2D simulations of groundwater flow and transport, showing the importance of incorporating information on the sediment accumulation processes into the hydraulic characteristics and how horizontal anisotropy emerging from these processes significantly influences transport. Effective hydraulic conductivity is modeled with a heterogeneous 2D anisotropic tensor with principal directions aligned with observed sedimentation sequences. Comparison of flow and solute dynamics simulated using reconstructed and theoretical hydraulic properties show drastically different pathways of solute propagation. Highlights: Depositional history in meandering channel deposits fundamentally affects solute fate. Channel stratal patterns yield heterogeneous and anisotropic conductivity. Horizontal anisotropies determine groundwater flow and solute pathways.